Economic Evaluation of Extended Early Intervention Service vs Regular Care Following 2 Years of Early Intervention: Secondary Analysis of a Randomized Controlled Trial. (12th September 2020) - Groff, Michael; Latimer, Eric; Joober, Ridha; Iyer, Srividya N; Schmitz, Norbert; Abadi, Sherezad; Abdel-Baki, Amal; Casacalenda, Nicola; Margolese, Howard C; Jarvis, G Eric; Malla, Ashok
Abstract: Cost-effectiveness studies of early intervention services (EIS) for psychosis have not included extension beyond the first 2 years. We sought to evaluate the cost-effectiveness of a 3-year extension of EIS compared to regular care (RC) from the public health care payer's perspective. Following 2 years of EIS in a university setting in Montreal, Canada, patients were randomized to a 3-year extension of EIS ( n = 110) or RC ( n = 110). Months of total symptom remission served as the main outcome measure. Resource use and cost data for publicly covered health care services were derived mostly from administrative systems. The incremental cost-effectiveness ratio (ICER) and cost-effectiveness acceptability curve were produced. Relative cost-effectiveness was estimated for those with duration of untreated psychosis (DUP) of 12 weeks or less vs longer. Extended early intervention had higher costs for psychiatrist and nonphysician interventions, but total costs were not significantly different. The ICER was 1627 per month in total remission. For the intervention to have an 80% chance of being cost-effective, the decision-maker needs to be willing to pay 5942 per month of total symptom remission. DUP ≤ 12 weeks was associated with a reduction in costs of 12 276 even if no value is placed on additional months in total remission. Extending EIS for psychosis for people, such as those included in this study, may be cost-effective if the decision-maker is willing to pay a high price for additional months of total symptom remission, though one commensurate with currently funded interventions. Cost-effectiveness was much greater for people with DUP ≤12 weeks.